2021
DOI: 10.18235/0003765
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Energy Transition on Employment: Today’s Results, Tomorrow’s Needs

Abstract: As countries progress in their energy transitions, new investments have the potential to create employment. This is crucial, as countries enter their post-pandemic recovery phase. An opportunity also arises to close the gender gap in the energy sector. However, how much will need to be invested, how many jobs will be created, and for whom, remain empirical questions. Little is also known about the needs of each country and their sectors in terms of future skills and training. The present work sheds light on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…A previous survey by the Inter-American Development Bank's (Ravillard et al 2021) identified a higher participation of women in emerging sectors in Latin America, including energy efficiency.…”
Section: Cumulative Energy Efficiency Investment In Buildingsmentioning
confidence: 99%
“…A previous survey by the Inter-American Development Bank's (Ravillard et al 2021) identified a higher participation of women in emerging sectors in Latin America, including energy efficiency.…”
Section: Cumulative Energy Efficiency Investment In Buildingsmentioning
confidence: 99%
“…Portanto, a etapa de implantação da cadeia energética nas diversas regiões do seu traçado, principalmente no local de O&M da UG, geram uma influência no desenvolvimento local agudo e crônico, ou seja, tem influência de LP, diferentemente das etapas pré-operacionaisestudo, projeto e construção -, em que os dois primeiros geram empregos e renda temporários, não necessariamente no local de implantação da cadeia energética, e o terceiro, mesmo sendo o mais intensivo em geração de empregos, possui um pico entre o segundo e o terceiro ano de implantação até se exaurir no seu término, persistindo no local apenas os empregos operacionais de O&M e serviços especializados para a UG (Ravillard et al, 2021), que também são menos intensivos, porém são de LP.…”
Section: Influência No Desenvolvimento Localunclassified